Study on Rapid Repair Method of Earthquake Damaged Pier Column Based on Multi-Level Fortification - Xiuli Xu; Lingxin Yan; Han Wu; Xu Chen; Shenpeng Xu; Xuehong Li (Buildings)
As a critical component of lifeline engineering, bridges play a vital role in post-earthquake rescue and disaster relief efforts. The rapid repair of earthquake-damaged piers is essential to ensure the uninterrupted functionality of lifeline systems. This paper presents a novel method for the rapid repair of earthquake-damaged pier columns using steel sleeves, based on a multi-level fortification approach, integrating numerical simulation, structural design, and experimental research. In alignment with the multi-level fortification requirements, the structural form of the outer steel sleeves was designed, key influencing factors were analyzed, and a design scheme for the outer steel sleeve was proposed. Furthermore, a quasi-static test was conducted to evaluate the seismic performance of the pier columns before and after repair. The results indicate that the maximum horizontal load the pier can withstand after repair is approximately 40% higher than that before the damage. When the pier’s bearing capacity reaches its maximum value, the horizontal displacement increases from 29.15 mm to 95.65 mm, indicating a significant improvement in the seismic performance of the repaired pier. Failure initiates with the buckling of the brace, followed by the buckling of the steel sleeves, demonstrating a multi-stage failure mode. This mode satisfies the requirements of multi-level fortification, with enhanced ductility achieved while maintaining the pier column’s bearing capacity, thereby enhancing the protection of the foundation.